Combustion temperature analysis in a fluidized-bed reactor by utilizing palm oil biomass for a renewable energy. Issue 1 (October 2021) - Erdiwansyah,; Mahidin,; Husin, Husni; Nasaruddin,; Muhibbuddin,; Faisal, M; Muhtadin,
Abstract: Biomass from palm oil is a renewable energy source that can be utilized and has very promising availability. Biomass energy is a renewable and sustainable energy that can replace conventional (fossil) fuels. The main objective of the experiment in this article is to analyze the combustion temperature, emissions, and efficiency of palm oil biomass fuel to use and applied in rural/remote areas. The palm oil biomass used in this study is palm kernel shells, empty fruit bunches, oil palm midrib, and oil palm fibers. The experiments in the research carried out in a fluidized-bed combustion chamber designed explicitly with capacities of up to 5 kg of biomass. The results of operations on fluidized-bed when the valve is open 100%, 75%, and 50% with overall palm oil biomass show a high combustion temperature. The highest combustion temperature was recorded in the TC test for 100% open valves with 3 kg biomass of 943°C. While the minimum combustion temperature obtained on TF2 at 50% open valve with 1 kg biomass of 619°C, overall combustion temperatures in this experiment showed high results. The maximum emission for O2 is 20.4% which is obtained at 50% open valve, while for CO2 the maximum emission is produced when 100% open valve is 19.9% with a biomass weight of 1 kg and 3 kg, respectively. The yield for maximum combustion efficiency when using 1 kg of biomass recorded at 50% open valve was 94.9%. While the minimum efficiency of 87.7% is obtained when the valve is 100% open with biomass of 2 kg. As the biomass fuel used in fluidized-bed increases, the combustion temperature also increases significantly.